Mandapa (pillared hall) of the Kumbheshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) of the Kumbheshwar Mahadev Temple is square in plan. Its main entrance is from the west, and the south and north sides have lateral wings protruding. These wings are semi-open like balconies. The exterior walls of the mandapa have minimal ornamentation. A band of kirtimukhas (face of glory) and peepal leaf motifs are the only ornamentation patterns on the wall.